Struggles and resilience: thalassemia patients navigating COVID-19 in Bangladesh - Farhin Islam; Senjuti Seemanta; Sonia Rezina; Afsana Mehrab; Enayetur Raheem; Mohammad Sorowar Hossain (Journal of Rare Diseases)
Abstract Purpose Bangladesh is located in the thalassemia-prone region geographically. Thalassemia patients need lifetime interdisciplinary care for their well-being. In COVID-19, many patients—especially those from developing nations—faced significant difficulties receiving treatment; including irregular transfusion frequency, iron chelation interruptions, blood shortages, and unsafe blood. This study will explore the multifaceted challenges faced by thalassemia patients in Bangladesh during the COVID-19 pandemic. Methods This cross-sectional study was an extension of an earlier investigation carried out at Bangladesh Thalassaemia Samity Hospital (BTSH). From the 365 cases of that first round, we could gather data from 156 cases in this second round. A structured questionnaire collected demographic information and thalassemia-related issues along with the impacts of COVID-19 on the patients and their families including the infection history with the virus, changes in income and/or expenditure, health status of the patient, mental health status of the mother, and difficulties in accessing healthcare services. Results Our findings suggest significant socioeconomic and health challenges during the COVID-19 pandemic among thalassemia patients’ families in Bangladesh. A substantial percentage of respondents faced income (n = 116, 74.35% experienced a decrease) and expenditure (n = 80, 51.28% experienced an increase) disruptions. Mental health challenges among mothers and difficulties in accessing healthcare services for the patients were prevalent. Among the 156 participants in our study, 35 families (22.44%) faced difficulties in managing blood or donors, 61 (39.1%) accessing services in hospitals or treatment centres, 49 (31.41%) managing regular follow-ups such as doctor visits and laboratory tests, 27 (17.42%) managing transportation for treatment purposes, and 27 (17.53%) managing money for treatment during COVID-19. Conclusions This study will help policymakers take need-based measures for this group of highly vulnerable people during such unprecedented times.